2021
DOI: 10.1109/jsyst.2020.3020155
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Co-Creative Problem Solving Toolbox in the Context of Norwegian High-Tech Industry

Abstract: Norwegian high-tech industries face a rapidly changing market need. Staying ahead of competitors and developing significant innovative solutions are essential for business value. Systems engineering has proven to be an effective approach for developing technical (hard) systems. People, organizations, and technical functionality contribute to an increasing complexity in today's high-tech systems. This makes the traditional systems engineering approach insufficient for innovation in a socio-technical context. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…-Introduce stakeholders to the Gigamap concept, highlighting its value as a visual tool for comprehending complex systems (Kjørstad et al 2021). -Clearly outline the co-design session's scope and objectives to ensure stakeholder alignment (Kjørstad et al 2021).…”
Section: System Mapping: An Essential Systemic Design Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…-Introduce stakeholders to the Gigamap concept, highlighting its value as a visual tool for comprehending complex systems (Kjørstad et al 2021). -Clearly outline the co-design session's scope and objectives to ensure stakeholder alignment (Kjørstad et al 2021).…”
Section: System Mapping: An Essential Systemic Design Toolmentioning
confidence: 99%
“…-Introduce stakeholders to the Gigamap concept, highlighting its value as a visual tool for comprehending complex systems (Kjørstad et al 2021). -Clearly outline the co-design session's scope and objectives to ensure stakeholder alignment (Kjørstad et al 2021). -Engage stakeholders in collaboratively mapping the system using the Gigamap, visualising its components and relationships (Davidová 2020).…”
Section: System Mapping: An Essential Systemic Design Toolmentioning
confidence: 99%
“…Figure 2 illustrates the research design. The first rectangle shows our previous work [33], where we identified the industry needs and the success criteria (Table 2). The two following rectangles of Figure 2 show the two stages of research presented in this article.…”
Section: Research Approachmentioning
confidence: 99%
“…The research presented in this article is part of a research collaboration project with four Norwegian high-tech industry partners and two academic partners in systems engineering and systems oriented design, respectively. In our former research, we identified that the industry needs to support rapid learning of systems knowledge through concept exploration, early validation, and knowledge transfer in the concept phase [33]. Furthermore, we explored the use of co-creative methods and tools [21,22,[34][35][36][37][38] to support the Norwegian high-tech industry in achieving their needs.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of the digital economy fuels innovative and productive national development activities in nations with advanced high-tech businesses. Promoting the balanced growth of high-tech businesses across different locations and increasing their innovation productivity should go without saying if we want to enhance the development of the high-tech sector [8][9][10]. Industrial digitalization can provide a new impetus for improving innovation efficiency in the digital economy era.…”
Section: Introductionmentioning
confidence: 99%